Distância entre passadas da colhedora com monitor de colheita nos mapas de produtividade e teor de água na cultura do milho - Bazzi, Claudio Leones (2007)
The precision agriculture comes in the last years enlarging its application in the country, seeking the increase of the productivity and profitability, also reducing the environmental impact with the appropriate application of fertilizers and agricultural inputs. The impediment for larger expansion of the technology is mainly the high cost of the equipments to be used. The generation of yield maps is the phase that presents larger execution easiness inside of the cycle of AP. However when several combines are working in a certain area, not always it is possible to have monitors in each one of them. In this context this work had as objective finds the step maximum number that it can be eliminated by the combine not equipped with yield monitor without quality loss in the yield and moisture maps generated. It was also looked for to accomplish a comparison among the interpolation methods inverse square root and Kriging. In the comparison between the simulated maps and the original, the coefficient of relative deviation was used - CDR and the index kappa. He/she was proven that the eliminated last number reduces the precision of the maps in both interpolation methods. The amount monitors that it should be had in a combine group, are relative at the level of precision that one want to have. The monitored combine should be inserted so that the samples are collected in an uniform way by the whole area to be crop.